Fast and Simple Construction of Efficient Solar‐Water‐Splitting Electrodes with Micrometer‐Sized Light‐Absorbing Precursor Particles. Issue 8 (9th September 2016) - Feng, Jianyong; Zhao, Xin; Ma, Su Su Khine; Wang, Danping; Chen, Zhong; Huang, Yizhong
Abstract : Micrometer‐sized light‐absorbing semiconductor particles (usually prepared by high temperature synthetic techniques) hold the desirable merits of high crystallinity, low concentrations of bulk defects, and a decreased grain boundary density to reduce bulk recombination of photocarriers. However, solar‐water‐splitting electrodes assembled using them as precursors always produce very low photocurrents. This could be due to the lack of an effective fabrication and/or modification protocol applicable to assemble these micrometer‐sized semiconductor particles into suitable electrode configurations. A fast and simple fabrication scheme of drop‐casting followed by the necking treatment is developed to enable the micrometer‐sized precursor particles derived photoelectrodes to deliver appreciable photocurrent densities (>1 mA cm −2 ). By applying this fabrication scheme, photoelectrodes of solid‐state reaction derived Mo doped BiVO4 (≈4 μm, modified with oxygen evolution catalysts) and commercial WO3 (size ranging from 100 nm to >10 μm) have yielded photocurrent densities higher than 1 mA cm −2, while the photoelectrode composed of commercial CdSe (≈10 μm) is able to produce a photocurrent density higher than 5 mA cm −2 (in a Na2 S aqueous solution). This strategy provides a new possible way, in addition to the predominant route of nanostructuring, to construct efficient solar‐water‐splitting electrodes. Abstract : A fast and simple fabrication scheme is developed to construct solar‐water‐splitting electrodes using micrometer‐sized light‐absorbing semiconductor particles, i.e., solid‐state reaction derived Mo doped BiVO4 (≈4 μm), commercial WO3 (particle sizes ranging from 100 nm to >10 μm), and commercial CdSe (≈10 μm). These photoelectrodes are able to deliver appreciable photocurrent densities (>1 mA cm −2 ).